Interest Rate Policy and Foreign Investors' Perceptions of Investment Risks in Indonesia: An Event Study Approach - Pramesti, Ginna Novarianti Dwi Putri (Economics Monetary Journal, 2025)
Changes in the benchmark interest rate by monetary authorities are often an important catalyst for financial market dynamics, particularly in influencing the risk perception of foreign investors in developing countries such as Indonesia. In this context, this study aims to analyze the influence of Bank Indonesia's interest rate policy on foreign investors' perception of investment risks, with an event study approach. This study uses secondary data that includes daily stock prices, exchange rates, and foreign capital flows during the period 2020–2023. The research sample consisted of companies listed on the Indonesia Stock Exchange and actively traded during the observation period. Data analysis techniques include calculation of abnormal returns (AR) and cumulative abnormal returns (CAR), as well as statistical testing with t-tests and Wilcoxon Signed-Rank. The results show that the announcement of interest rate cuts consistently results in abnormal positive returns and increased foreign capital flows, while interest rate hikes lead to abnormal negative returns and capital withdrawals by foreign investors. A significant market response mainly occurred on the 1st to 3rd day after the announcement, which shows the market efficiency of the semi-strong form. These findings confirm that interest rate policy has a high information value and directly influences the risk perception of foreign investors. The practical implications of this study underscore the importance of transparency and consistency of monetary policy communication to maintain market stability and investment attractiveness in Indonesia.